2018
DOI: 10.1111/pde.13550
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in fifth‐grade sun protection: Evidence from the Healthy Passages study

Abstract: Our data confirm low use of sun protection among fifth-graders. Future research should explore how public health success in increasing prevalence of other preventive health behaviors may be applied to enhance sun protection messages. Identifying risk factors for poor adherence enables providers to target patients who need more education. Improving educational policies and content in schools may be an effective way to address sun safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Prevention of melanoma relies heavily on sun protection, especially in childhood [9,10]. However, there is a lack of sun protection in primary school children [11,12].…”
Section: Background and Rationalementioning
confidence: 99%
“…Prevention of melanoma relies heavily on sun protection, especially in childhood [9,10]. However, there is a lack of sun protection in primary school children [11,12].…”
Section: Background and Rationalementioning
confidence: 99%
“…Studies that assessed knowledge and behaviors found that racial minorities, particularly Hispanics and Blacks, have lower knowledge and practice less effective sun protection behaviors. [31][32][33][34][35] Bandi et al 36 found race and ethnicity are significantly associated with the frequency of sun protection counseling by providers. Non-White, non-Hispanic, and Hispanic patients of any race are less likely to receive sun protection counseling (OR = 0.58) compared with White, non-Hispanic counterparts.…”
Section: Acnementioning
confidence: 99%
“…In the school setting, a study by Correnti et al showed inadequate youth sun-protective behavior (eg, sunscreen use) despite rising skin cancer rates in children. 6 Pollitt et al further explored sun-protective behavior specifically in low socioeconomic (SES) status population. The study focused on the association of low socioeconomic status with more advanced melanoma at diagnosis and decreased survival.…”
Section: Thementioning
confidence: 99%